2014
DOI: 10.1242/dev.110163
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic DNA methylation cycle from egg to sperm in the honey beeApis mellifera

Abstract: In honey bees (Apis mellifera), the epigenetic mark of DNA methylation is central to the developmental regulation of caste differentiation, but may also be involved in additional biological functions. In this study, we examine the whole genome methylation profiles of three stages of the haploid honey bee genome: unfertilised eggs, the adult drones that develop from these eggs and the sperm produced by these drones. These methylomes reveal distinct patterns of methylation. Eggs and sperm show 381 genes with sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
55
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 53 publications
9
55
1
Order By: Relevance
“…Finally, many cytosines were methylated in one sample only, due to either biological or experimental variation. By applying the statistical methods used in previous studies [14, 6] to our data, we show that such sample-specific DNA methylation may underlie the previous findings of queen- and worker-specific methylation. We argue that there is currently no evidence that genome-wide variation in DNA methylation is associated with the queen and worker castes in social insects, and we call for a more careful interpretation of the available data.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Finally, many cytosines were methylated in one sample only, due to either biological or experimental variation. By applying the statistical methods used in previous studies [14, 6] to our data, we show that such sample-specific DNA methylation may underlie the previous findings of queen- and worker-specific methylation. We argue that there is currently no evidence that genome-wide variation in DNA methylation is associated with the queen and worker castes in social insects, and we call for a more careful interpretation of the available data.…”
supporting
confidence: 60%
“…There was no exon that was consistently differentially methylated between phases in all four source colonies. This shows that the statistical method used in previous studies, especially when used without biological replicates [14, 6], is prone to return random or colony-specific lists of exons. See also Figure S3.…”
Section: Figurementioning
confidence: 99%
“…Although we have no direct evidence to suggest a role for DNMT1 in imprinting, it is notable that eusocial life and haplodiploidy present a number of evolutionary conflicts between males and queens (Drewell et al, 2012;Galbraith et al, 2016). Moreover, eggs and sperm have been shown to exhibit differences in DNA methylation at several hundred genes in A. mellifera (Drewell et al, 2014), and differences in the expression of A. mellifera matrigenes and patrigenes have recently been documented (Galbraith et al, 2016). Nevertheless, a recent investigation of Nasonia revealed no direct evidence for parent-of-origin differentially methylated regions, which casts doubt on the DNA methylation-imprinting hypothesis in hymenopteran insects (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 72%
“…Indeed, a previous analysis revealed rank correlations greater than 0.9 between mean coding sequence DNA methylation levels of distinct fire ant castes and sexes, as well as between A. mellifera brains and whole body samples (Table S4 in Hunt et al, 2013b). Similarly, the commonalities in DNA methylomes from A. mellifera sperm, eggs, and adult males vastly outnumber the differences (Drewell et al, 2014). Thus, we hypothesize that most de novo DNA methylation occurs during embryonic, rather than postembryonic, development, and that DNMT3 is performing de novo DNA methylation in S. invicta.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, aspects of honey bee defensiveness (Guzman-Novoa et al, 2005) and reproductive physiology (Jordan et al, 2008a;Linksvayer et al, 2009;Beekman et al, 2012;Oldroyd et al, 2014) are more strongly transmitted via males than via females. Honey bees have a fully functional DNA methylation system (Wang et al, 2006;Foret et al, 2009) and differential methylation depending on parent-of-origin could explain the observed effects of sire (Drewell et al, 2012;Drewell et al, 2014;Oldroyd et al, 2014). We found that two colonies headed by F 1 queens backcrossed to Scutellata drones produced a similar proportion of offspring thelytokously (21 thelytokous vs 6 arrhenotokous) as two colonies headed by F 1 queens backcrossed to Capensis drones (37 thelytokous vs 21 arrhenotokous; χ 2 1 = 1.662, P = 0.197).…”
Section: Discussionmentioning
confidence: 99%